2018
DOI: 10.1039/c8ra00721g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on Leymus chinensis seedlings under salt–alkali stress and nitrogen deposition conditions: from osmotic adjustment and ion balance

Abstract: We evaluated the contribution of arbuscular mycorrhizal fungi to the growth, ion content, and solute accumulation of Leymus chinensis seedlings under salt–alkali stress and nitrogen deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…Plants can accumulate osmotic adjustment substances, which is an effective way to alleviate osmotic stress cause by AS (Lin et al, ). Many of these osmotic adjustment substances are N ‐containing compounds, such as amino acids, amides, and betaines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can accumulate osmotic adjustment substances, which is an effective way to alleviate osmotic stress cause by AS (Lin et al, ). Many of these osmotic adjustment substances are N ‐containing compounds, such as amino acids, amides, and betaines.…”
Section: Discussionmentioning
confidence: 99%
“…In the northeast of China, alkaline meadows cover >70% of the land, and the area continues to expand (Lin, Wang, Sun, Mu, & Yan, 2017). Alkaline stress (NaHCO 3 or Na 2 CO 3 ) is more severe than saline stress due to its unique high pH, which can inhibit ion uptake and disrupt the ionic balance of plant cells (Lin et al, 2018;Yang, Zheng, Tian, Wu, & Zhou, 2011). However, some halophytes in northern China, including Puccinellia tenuiflora, Leymus chinesis, and Suaeda glauca, have evolved various regulatory and metabolic mechanisms and can naturally survive in alkali-degraded soil.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that alkaline salt stress and neutral salt (e.g., NaCl and Na 2 SO 4 ) stress are actually two entirely different stress types [5][6][7]. Alkaline stress not only has the same inhibitory effects as saline stress but also has the unique influence of high pH, which inhibits ion uptake and disrupts the ionic balance of plant cells [8,9]. However, to the best of our knowledge, the majority of studies have emphasized the toxic effects of salt stress and paid little attention to alkaline stress, and the specific alkali-tolerance mechanisms of halophytes are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium is one of the most dominating toxic ions that induce soil salinization. Extremely accumulated Na can induce ionic imbalance and disrupt normal physiological metabolisms ( Lin et al, 2018 ; He et al, 2020 ). Our observations showed that Na was significantly accumulated in plants in both S. salsa community and P. tenuiflora community, indicating that these plants can survive from excess Na from soils.…”
Section: Discussionmentioning
confidence: 99%